THE EFFECTIVENESS OF TASK-BASED LANGUAGE TEACHING IN UNIVERSITY EFL CLASSROOMS (International journal of artificial intelligence, 2026)
The development of communicative competence has become one of the major goals of modern English as a Foreign Language (EFL) education. Traditional teacher-centered methods often fail to provide students with sufficient opportunities for meaningful interaction and real-life communication. As a result, Task-Based Language Teaching (TBLT) has gained significant attention as an effective learner-centered approach. This study investigates the effectiveness of TBLT in university EFL classrooms and examines its influence on students’ communicative competence, motivation, and classroom participation. The study employs a qualitative descriptive approach supported by classroom observations and student feedback collected from university EFL learners. Findings indicate that task-based activities encourage active participation, improve speaking confidence, and create a more engaging learning environment. Students demonstrated increased motivation and greater willingness to communicate during collaborative tasks. However, several challenges were identified, including time management difficulties, varying proficiency levels, and classroom organization issues. Despite these limitations, the study concludes that TBLT significantly contributes to the development of communicative skills and learner autonomy in higher education settings. The paper recommends the systematic integration of task-based activities into university EFL curricula to promote interactive and meaningful language learning.